2021
DOI: 10.1002/jsfa.11522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vine top shading on the accumulation of C6/C9 compounds in 'Cabernet Sauvignon’ (Vitis vinifera L.) grape berries in northwestern China

Abstract: BACKGROUND: The Xinjiang Uygur Autonomous Region is an arid and semi-arid region with low rainfall and strong sunlight; thus, grape berries in this region accumulate sugar content rapidly, and the ripening process is shorter than that in other regions. Although previous studies illustrated that altered sunlight conditions could influence the aroma profiles of grape berries, less attention has been paid to the effect of vine top shading on volatile compounds under a dry-hot climate.RESULT: We focused on the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…There is an important impact of vine shading on C6/C9 compound biosynthesis (products of the lipoxygenase pathway) and on the concentrations of linolenic and linoleic acids. Under detected high temperatures, the outflow of isoprene, monoterpenes, and C6 elements can balance photosynthetic membranes, preserving the photosynthetic apparatus from lipid peroxidation damage [57]. In addition, shading of the 'Muscat' bunch and leaves from the berry setting to harvest enhanced the concentration of hexanal (C 6 H 12 O) and (E)-2-hexenal compounds [58].…”
Section: Introductionmentioning
confidence: 99%
“…There is an important impact of vine shading on C6/C9 compound biosynthesis (products of the lipoxygenase pathway) and on the concentrations of linolenic and linoleic acids. Under detected high temperatures, the outflow of isoprene, monoterpenes, and C6 elements can balance photosynthetic membranes, preserving the photosynthetic apparatus from lipid peroxidation damage [57]. In addition, shading of the 'Muscat' bunch and leaves from the berry setting to harvest enhanced the concentration of hexanal (C 6 H 12 O) and (E)-2-hexenal compounds [58].…”
Section: Introductionmentioning
confidence: 99%
“…A comparison with existing literature reveals that the presence and concentration of C9 aldehydes in grapes are influenced by a multitude of factors, including genetic varietal characteristics, viticultural practices, and, notably, climatic conditions [27,28]. Studies have highlighted the sensitivity of C9 aldehyde synthesis to environmental factors, suggesting that variations in temperature, sunlight exposure, and rainfall can significantly affect their accumulation in grapes [29]. The meteorological data presented for the vintages 2019 and 2020 (Table S1) provide critical insights into the climatic backdrop against which these aromatic compounds developed.…”
Section: Green Leaf Volatile Evolutionmentioning
confidence: 99%
“…The results showed that shading had significant effects on leaf growth and photosynthetic characteristics, but there were differences among species [18]. In the study of grape berries, the impact of shading during berry ripening on the tannin structure-activity relationship of berry skin extracts was examined, as well as the effect of vine roof shading on C6/C9 compound accumulation in the northwest grape variety 'Cabernet Sauvignon' (V. vinifera L.) [19]. The berries were the main focus of the study.…”
Section: Introductionmentioning
confidence: 99%